KAOLINITE CLAY AS GREEN AND SUSTAINABLE RAW MATERIAL FOR ZEOLITES PRODUCTION: A REVIEW - Jacob, Adikwu Gowon; Alisi, Ikechukwu Ogadimma; Surajo, Jikamshi Mustapha (FUDMA JOURNAL OF SCIENCES, 2025)
This review explored the potential of kaolinite clay as a green and sustainable raw material for the production of zeolites. Clay is a naturally abundant and inexpensive mineral, with unique properties that make it an ideal precursor for zeolite synthesis. The review discussed the properties and applications of clay minerals, as well as the preparations and applications of metakaolin, the thermally activated form of kaolinite clay. Furthermore, the review delved into the properties, structures, types, and methods of preparation of zeolites from metakaolin. Applications of zeolites in various fields, including catalysis, adsorption, and environmental remediation were highlighted. Moreover, the various characterization methods for zeolites including X-ray diffraction, scanning electron microscopy, X-ray fluorescence (XRF) and nitrogen adsorption-desorption analysis were also discussed. Obviously, the review have provided a comprehensive understanding of the potential of kaolinite clay as a sustainable raw material for zeolite production. Findings of the study will not only advance the understanding of zeolite production from kaolinite clay, but will also promote their industrial applications.
Keywords: Applications; Characterization; Clay minerals; Kaolinite clay; Zeolites